PENGARUH BEBERAPA PERLAKUAN TERHADAP MASA DORMANSI BIJI BELIAN (Eusideroxylon zwageri T.et.B) - Chyntia, Puspaningrum; Abdurrani, Muin; Reine, Wulandari Suci (Universitas Tanjungpura, 2013)
Type belian increasingly threatened by logging, followed by rejuvenation, while growth is known to be very slow. One to maintain the standing purchase is to cultivate these plants. Purchase seed coat is very hard, it should be given a variety of treatments. The purpose of this study was undertaken to determine the effect of several treatments that can overcome dormancy in seed purchase and finding the right treatment to break seed dormancy diamond. This research was conducted at the Laboratory of Silviculture Faculty of Forestry, University of Tanjungpura Pontianak, a study carried out for about 3 (three) months. This research method used is Randomized Block Design Acak (RAK), which consists of 5 treatments and 4 replications. The treatment consists of treatment research P0 (control), P1 (skin solving in seeds), P2 (soaking seeds with 70% H2SO4), P3 (soaking seeds with auxin), and P4 (soaking with GA) with each of treatment 3 subsampling. Mean while, as the length of the seed is made ??up of a group I = 8 cm - 8.9cm, group II = 9 cm - 9.9 cm, group III = 10.1 cm - 10, 8, and group IV = 11 cm - 12.8 cm. Friedman Test results of calculations obtained from treatment that do not significantly affect seed dormancy period on purchases. From the results of Friedman test value T = 8 is smaller than the = 9.49, it was decided to accept H?. In the treatment P0 gives a good change (seeds still in good condition and had cracking), whereas the other treatments the seeds die.Keyword : Eusideroxylon zwageri T.et.B, Dormancy, H2SO4, Plant Growth Regulation